2001
DOI: 10.1139/x01-123
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early tree height in forest genetic trials is enhanced by including a spatially correlated residual

Abstract: This study explores the use of a mixed linear model including spatially correlated residuals in addition to the traditional randomized complete block (RCB) analysis in 12 forest genetic trials. The analysis of early height data from progeny and clonal tests of three species (Picea sitchensis (Bong.) Carr., Pinus pinaster Ait., and Pinus radiata D. Don) showed that there was significant spatial variation in all trials. Adding a basic first-order separable autoregressive error term more effectively modelled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…However, experimental studies with large number of trials and variables have shown that either an increase or decrease is possible for σ 2 A using spatial analyses. Our observations of increased additive variance in most cases and decreased variance in some cases are in line with those reports with many trials and variables (Costa e Silva et al 2001;Dutkowski et al 2002Dutkowski et al , 2006Ye and Jayawickrama 2008). There may several possibilities with decreased genetic variance in spatial model.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, experimental studies with large number of trials and variables have shown that either an increase or decrease is possible for σ 2 A using spatial analyses. Our observations of increased additive variance in most cases and decreased variance in some cases are in line with those reports with many trials and variables (Costa e Silva et al 2001;Dutkowski et al 2002Dutkowski et al , 2006Ye and Jayawickrama 2008). There may several possibilities with decreased genetic variance in spatial model.…”
Section: Discussionsupporting
confidence: 93%
“…(2) A spatial model using an autoregressive spatial component and an independent error instead of just an independent error in base model (Costa e Silva et al 2001;Dutkowski et al 2002) as…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations